Solid grain migration on hydraulic properties of fault rocks in underground mining tunnel: Radial seepage experiments and verification of permeability prediction. (August 2022) - Ma, Dan; Duan, Hongyu; Zhang, Jixiong
Highlights: Water-conducting channels are prone to forming in the fault, causing water inflow. Evolution of hydraulic properties under the radial grain migration was studied. Low GSD and high WP can enhance the grain migration effect. Three permeability predicted models were verified by the testing results. Strategies for the prevention and control of water inflow were proposed. Abstract: When fault fracture zones are encountered in the mining tunnel excavation, the water-conducting pathway is easily formed by the granular structure of the broken surrounding rock, probably resulting in water inflow hazards. Therefore, the configuration and hydrological characteristics of existing faults are key factors for the safe mining tunnel construction. In this paper, one-dimensional (1D) radial seepage experiments were carried out under variable grain size distribution (GSD) and water pressure (WP). Hydraulic properties were investigated, including porosity and permeability under the 1D radial grain migration. Experimental results show that the permeability and porosity increase with time, and the occurrence process of water inflow can divide into four stages, including the rapid increase, decelerated increase, slow climbing, and stable period. After the seepage experiment, the porosity of the sample increases gradually from the top to the bottom and reaches the maximum at the lowermost part (outlet), indicating that the spatial distribution of the porosity exhibits the non-uniform property. Through comparisons of grain migration under different conditions, it is concluded that, with the decrease of GSD and the increase of WP, more severe fine grain migration can be occurred, leading to great changes in hydraulic properties. In addition, three prediction models were verified by the testing results, and Carman-Kozoeny model shows the highest accuracy. In the same predictive model, if a sample has a smaller grain migration capacity, then there is a higher prediction accuracy of the sample. By means of Carman-Kozoeny model, it is predicted that there is a higher final permeability in the position closer to the water outlet. Based on the research results, a series of strategies were proposed to prevent and control water inflow in fault rocks.